Information and Communication Technologies in Benefit of Educational Innovations - DJELTI, Mohammed; KHEDDAR, Hamza (Journal of Human Sciences, 2025)
The rapid digital transformation of educational systems, notably accelerated by the COVID- 19 pandemic, has necessitated innovative teaching methods to accommodate the surge in online education. This paper explores the integration of Information and Communication Technologies (ICT) in education, focusing on their application in creating flexible, multimodal learning environments that enhance student engagement and participation. Specifically, we examine the effectiveness of various pedagogical innovations such as e-learning, m-learning, blended learning, flipped classrooms, BYOD policies, and MOOCs. Our analysis is based on a survey conducted with 200 students from the National Higher School of Telecommunications and ICT in Oran, Algeria, assessing their experiences and satisfaction with these modalities. The study highlights the critical role of ICT in facilitating accessible, inclusive, 9 and effective learning solutions and discusses the challenges and opportunities that lie ahead in the context of educational innovations. This work not only underscores the evolving landscape of educational methodologies but also provides insights into future directions for leveraging technology to improve learning outcomes.